Phytochemical, Antimicrobial and Cytotoxic Activities of Gaultheria Trichophylla Royle - Shah Zaman; Fakhria A. Al-Joufi; Muhammad Zafar; Muhammad Zahoor (Applied Sciences, 2022)
Gaultheria trichophylla fruit is used by the indigenous people to treat asthma, headache, and as an appetizer in the alpine and sub-alpine regions of Western Himalaya. No studies exist on the antimicrobial significance of this species. The current study describes the phytochemical composition, in vitro cytotoxic, and antimicrobial effects of different extracts of Gaultheria trichophylla. In antimicrobial assay, four different bacterial strains (Escherichia coli, Bacillus subtilis, Pseudomonas aeruginosa, and Staphylococcus aureus) as well as four fungal strains (Helminthosporium solani, Fusarium solani, Aspergillus flavus, and Aspergillus fumigates) were used. Qualitative phytochemical screening showed the existence of different active compounds. Quantitative phytochemical screening showed the existence of phenolic contents in the range from 3.27 ± 0.44 mg GE/g to 14.17 ± 088 mg GE/g, whereas flavonoids were from 8.08 ± 0.48 mg QE/g to 26.9 ± 0.23 mg QE/g. The elemental analysis quantified essential minerals of life importance such as Na (3.24 ± 0.05 µgg−1), Mg (1.93 ± 0.08 µgg−1), and Ca (1.83 ± 0.056 µgg−1), while none of the heavy metal levels were high from the permissible limit of WHO. Cytotoxic assay showed moderate activity in terms of LC50 of (50 μg/mL) for methanolic extracts. Antifungal assay of methanolic and other extracts against different tested fungal strains showed a zone of inhibitions from 29 ± 1.154% to 86.66 ± 0.09%. As an antibacterial, the MIC values were from 7.5 mg/mL to 15 mg/mL for the tested extracts. The observed biological potentials were at the expense of its phytochemical composition, however, further confirmation in animal models and responsible phytochemical isolations in pure form is needed.